(untitled) (Journal of Enam Medical College, 2014)
Background: Carcinoma of cervix is the most common malignancy in female and a major public health problem worldwide. It is the leading cause of death from cancer among women in low resource settings. In Bangladesh, mortality rate is high as most of the cases with cervical cancer are diagnosed in advanced stage. World Health Organization considers cervical cancer as a preventable disease as it can be identified in preinvasive stage. Considerable efforts have been given in detection and treatment of the condition all over the world. A number of cervical cancer screening tests are available. Among them, visual inspection of cervix with acetic acid is rational and can be competently performed by physicians with proper training. Objective: To find out the feasibility of the visual inspection of cervix with acetic acid for the detection of the precancerous lesions of the cervix in our country. Materials and Methods: This cross sectional, analytical study was carried out among the patients attending the outpatient department of Bangabandhu Sheikh Mujib Medical University (BSMMU) who were VIA positive and sent for colposcopy in the colposcopy clinic in the department of Obstetrics and Gynecology in BSMMU from June to December 2004. Two hundred samples were considered for this study. Results: Out of 200 cases, colposcopically 85% had CIN and invasive lesions, 4% had inflammatory lesions while 11% had normal findings. Colposcopy directed punch biopsy revealed positive lesions in 81%, 4% had inflammatory lesions while 15% had normal findings. Conclusion: The study concluded that VIA and colposcopy are the important methods in the evaluation of cervical premalignancy. VIA may be an important tool for screening of cervical cancer in low resource settings as it is simple, easy to perform and cost-effective. After screening, VIA positive cases must be referred for colposcopic evaluation. We can screen cervical cancer by VIA all over the country and thus reduce morbidity and mortality rate. DOI: http://dx.doi.org/10.3329/jemc.v4i1.18068 J Enam Med Col 2014; 4(1): 39-44